Analisis Based Social Entreprenuership Pada Pondok Pesantren Al Fusha Pekalongan - Vici Prihmaningrum; Silfiani Silfiani; Ageng Widodo (Mafa Press, 2023)
This study aims to determine the implementation of social entrepreneurship at the Al Fusha Integrated Islamic Boarding School. This study uses a qualitative-descriptive method, with interviews, observations, and literature review as instruments. The results of the study indicate that entrepreneurial activities at the Al Fusha Integrated Islamic Boarding School are a model of social entrepreneurship. The benchmark of social entrepreneurship in Al Fusha can be seen through the process of social entrepreneurship which includes antecedents, entrepreneurial orientation, and outcomes. The antecedents stage begins with formulating a social mission, namely educating students and spreading benefits for the community. The mission is based on social problems which are then used as a business opportunity. Second, entrepreneurial orientation, Al Fusha Islamic boarding school in developing its business creates social innovation and risk taking so that the business can continue to grow to achieve the goals it wants to achieve. The last stage is the outcome, the social value created has an impact on students and also the community. There are supporting and inhibiting factors for social entrepreneurship activities that come from external and internal sources.